Anions Stabilize Each Other inside Macrocyclic Hosts. (6th October 2016) - Fatila, Elisabeth M.; Twum, Eric B.; Sengupta, Arkajyoti; Pink, Maren; Karty, Jonathan A.; Raghavachari, Krishnan; Flood, Amar H.
Abstract: Contrary to the simple expectations from Coulomb's law, Weinhold proposed that anions can stabilize each other as metastable dimers, yet experimental evidence for these species and their mutual stabilization is missing. We show that two bisulfate anions can form such dimers, which stabilize each other with self‐complementary hydrogen bonds, by encapsulation inside a pair of cyanostar macrocycles. The resulting 2:2 complex of the bisulfate homodimer persists across all states of matter, including in solution. The bisulfate dimer's OH⋅⋅⋅O hydrogen bonding is seen in a 1 H NMR peak at 13.75 ppm, which is consistent with borderline‐strong hydrogen bonds.